Aplicación de la herramienta Sotfware Abriltronic, basado en la Teoria de Polya, para mejorar la capacidad de Resolución de Problemas Matemáticos de las cuatro operaciones básicas en los alumnos del 3° grado de Primaria de la I.E. Ramón Castilla Marquezado – Alto Trujillo - Araujo Valderrama, Karen Thaiz (2017)
The present research work entitled "Application of the software tool Abriltronic, based on the theory of Polya, to improve the ability to solve mathematical problems of the four basic operations in students of the 3rd grade of primary education in the I.E. Ramón Castilla Marquezado - Alto Trujillo ", was oriented by the general objective that was to determine if the application of Abriltronic Software Tool, based on the theory of Polya, manages to improve the ability to solve mathematical problems of the four basic operations._x000D_ We used the quasi experimental design, we worked with two sections of the I.E. Ramón Castilla Marquezado one directed to be our control group, which counted on 32 children and the experimental group with 30 children that is to say worked with a sample of 62._x000D_ After processing all the data and their presentation in tables, graphs and their description, as well as the calculation of statistical means of central tendency and variability, to culminate with the test of hypotheses applying the statistic t of Student, the discussion of results allowed to obtain As the main conclusion the following:_x000D_ When comparing the before and after application of the Software Tool "Abriltronic", in the experimental group a positive percentage difference was determined, since at the start level it decreased by 19.2%, ie in its entirety, in the level of Process has decreased by 57.7%, on the other hand the expected level of achievement has increased by 53.9% and in the last level we can see that there was no percentage, but after applying the Software Tool "Abriltronic has increased.